Crisis-driven digital transformation as a trigger for process virtualization: Fulfilling knowledge work process requirements for remote work. (June 2023) - Zeuge, Anna; Schaefer, Cindy; Weigel, Andreas; Eckhardt, Andreas; Niehaves, Bjoern
Abstract: Process Virtualization Theory (PVT) proposes a set of requirements and relationships to explain and predict whether or not a knowledge work process can be successfully virtualized. However, at least in remote work, the crisis-driven digital transformation (e.g., during the COVID-19 pandemic) shows that almost all knowledge work processes can be virtualized unexpectedly and immediately. Since the requirements for these processes remain the same and need to be met to continue the processes remotely, an interesting question arises of how information technology (IT) can help to meet these requirements in a crisis-driven digital transformation of knowledge work. To address this question, we conducted 40 semi-structured interviews with a multiple-case approach using a critical realist perspective. Our findings contribute to information systems (IS) research in a twofold way. First, we demonstrate that the crisis-driven digital transformation of knowledge work triggers a revisited perspective on PVT by turning virtualized knowledge work processes into a prerequisite. Second, we show how the IT characteristics of PVT (representation, reach, monitoring capability) help to fulfill knowledge work process requirements in remote work settings and outline two additional IT characteristics (social presence and situation awareness) that positively support the fulfillment. Highlights: Crisis-driven revisited perspective on Process Virtualization Theory (PVT). Dependent factor "Process Virtualizability" in PVT turns into a prerequisite. IT characteristics of PVT help to fulfill virtualized KWP requirements. Extension of PVT by new IT characteristics (social presence/situational awareness). Explorative multiple case approach including 40 semi-structured interviews.